Gems of wisdom words of inspiration - Satchidananda, Swami, 1914-2002. (Buckingham, Va. : Integral Yoga Publications, 2011)
Short, inspiring passages excerpted from other books of Swami Satchidananda, including Beyond Words, To Know Yourself, and The Golden Present. Topics include Discipline, Faith, God, Happiness, Health & Healing, Love, Mantra & Meditation, Marriage, Peace, Prayer, Religion, Right Action, Right Thinking, Selfless Service, Spiritual Practice, Surrender, Teacher & Teaching. Short passages which deliver profound wisdom and practical guidance full of love, grace, humor, and inspiration. ?A yogi is like a surfer who knows how to balance on the surfboard? Above all, there should be peace, tranquility, and acceptance in everything you do. Then you will see that your whole life is transformed.?
"Gems of wisdom was excerpted from these books by Sri Swami Satchidananda: Beyond words, To know your self, The golden present."
Keywords: Conduct of life; Spiritual life; Yoga; SELF-HELP / Personal Growth / Happiness; RELIGION / Prayer; RELIGION / Sermons / General; Electronic books